The Impact of the digitalization and the policy changes on the Savings Instruments (Saving Certificates) in Bangladesh: a response from the investors. - Basak, Ashish (International Journal of Scientific Research and Management (IJSRM), 2021)
Investment in the National Savings Certificate (NSC) has been the most popular savings instrument among the people of Bangladesh that provides guaranteed returns with tax savings. The government of Bangladesh mainly issues the NSCs to collect money from small and scattered savings of general people. It brings marginal and special populations into the Government's social safety net programs for ensuring an equitable and poverty-free society. Recently the authority has introduced automation and regulatory deterrents such as making mandatory the submission of e-TIN, national identity cards, bank accounts, cheque transactions, and increased deduction at source. My research has attempted to identify the impact of the policy changes on the investors’ minds and how they react. This study suggests that recent policy changes and the requirement for the mandatory documents to purchase NSCs have no impact on the investment decision as people still consider this is the most attractive and secures means of investment.